Extensive chromosomal reshuffling drives evolution of virulence in an asexual pathogen - de Jonge, Ronnie; Bolton, Melvin D.; Kombrink, Anja; van den Berg, Grardy C.M.; Yadeta, Koste A.; Thomma, Bart P.H.J. (Genome Research, 2013)
Sexual recombination drives genetic diversity in eukaryotic genomes and fosters adaptation to novel environmental challenges. Although strictly asexual microorganisms are often considered as evolutionary dead ends, they comprise many devastating plant pathogens. Presently, it remains unknown how such asexual pathogens generate the genetic variation that is required for quick adaptation and evolution in the arms race with their hosts. Here, we show that extensive chromosomal rearrangements in the strictly asexual plant pathogenic fungus Verticillium dahliae establish highly dynamic lineage-specific (LS) genomic regions that act as a source for genetic variation to mediate aggressiveness. We show that such LS regions are greatly enriched for in planta-expressed effector genes encoding secreted proteins that enable host colonization. The LS regions occur at the flanks of chromosomal breakpoints and are enriched for retrotransposons and other repetitive sequence elements. Our results suggest that asexual pathogens may evolve by prompting chromosomal rearrangements, enabling rapid development of novel effector genes. Likely, chromosomal reshuffling can act as a general mechanism for adaptation in asexually propagating organisms.
10.1101/gr.152660.112